Diskursi feminizma i modernizma u esejima Julke Chlapec Đorđević i Jele Spiridonović-Savić - Đurić, Dubravka (Wydawnictwo Nauka i Innowacje, 2014)
I start from the definition of Serbian Yugoslav bourgeois culture as a semi-peripheral and having this in mind, I tend to analyze the essays by Julka Chlapec Đorđević and Jela Spiridonović-Savić, from the perspective of the world systemic theories applied to literature.
Discourses of Feminism and Modernism in the Essays of Julka Chlapec Đorđević and Jela Spiridonović-Savić
Keywords: anti-modernism; feminism; modernism; semi-periphery